Scoring System for Predicting No Hearing Recovery in Unilateral Idiopathic Sudden Sensorineural Hearing Loss - Eka Dian Safitri; Kuntjoro Harimurti; Respati W Ranakusuma; Widayat Alviandi; Jenny Bashiruddin; Ary I Safitri (Acta Medica Indonesiana, 2023)
Background: The varying degrees of hearing recovery in idiopathic sudden sensory neural hearing loss (ISSHL) patients indicate the need of model to predict no hearing recovery. We aimed to aid in the counseling of ISSHL patients about their recovery chances by developing a simple clinical scoring system to predict no hearing recovery using clinical information available at first visit. Methods: A retrospective cohort study, using medical records was conducted from January 2017-May 2019 in Cipto Mangunkusumo General Hospital and Proklamasi Ear, Nose, Throat, Head and Neck (ENT-HN) Surgery Specialized Hospital in Jakarta, Indonesia. The outcome measure is no hearing recovery and we built the prediction score developed based on multiple logistic regression analyses and tested for discriminative ability. There were 183 adults unilateral ISSHL patients included in the study. Results: The proportion of no hearing recovery was 56%. The independent predictors were older age 30-60 years and >60 years old (Odds Ratio 4.0; 95% CI 1.4-11.8; p=0.012 and OR 5.3; 95% CI 1.5-18.4; p=0.008, respectively) as compared with 18-<30 years old, later onset (onset 15-60 days and >60 days had OR 5.4; 95% CI 1.7-16.9; p=0.004 and OR 12.6; 95% CI 2.9-54.6; p=0.001, respectively, as compared with onset < 3 days), and presence of vertigo (OR 2.3; 95% CI 1.1-4.6; p=0.026). Prediction scores ranged from 3 to 12, with three categories for age, four for onset, and two for the presence of vertigo. The predictions showed adequate calibration and good discriminative ability (AUC 0.77). Conclusion:Using information of age, onset and presence of vertigo at first visit, ISSHL patient with increased risk of no hearing recovery can be identified with moderate accuracy. This prediction model could help clinician in predicting patients’ prognosis.